The Use of Technology in Enhancing Social Studies Learning: a Review of Current Trends and Research Findings - Iswan Riyadi (Universitas Muhammadiyah Enrekang, 2023)
Supporting factors in the learning process are needed: technology that is able to improve the quality and quantity of learning and is able to help teachers understand students' interest in learning social studies. Technology that can help teachers and students to use media. Finding out how technology may help students succeed in social studies was the focus of this research. Teachers and students both stand to benefit from increased access to and usage of technologically advanced instructional materials. In this research, a literature review method was used. Grounded theory research, which in this case investigates the use of technology in social studies education, is conducted with the overarching goal of comprehending ideas that ultimately constitute theory. The findings of this research suggest that educators and their students may benefit from making better use of technology in the classroom. Educators' willingness and skill in using learning models to further education must keep pace with technology's fast improvement.